(untitled) (Ideal Journal of Multidisciplinary Research, 2026)
The text of the article covers the issues of individual psychological characteristics of teenagers, the psychological impact of false religious information on the psyche of teenagers. The importance of effective means of preventing teenagers from falling under the influence of various foreign ideas and showing them the right way has been analyzed.